New genus and species of the Yuripopovinidae (Pentatomomorpha: Coreoidea) from mid-Cretaceous Burmese amber. (February 2019) - Du, Sile; Hu, Zhengkun; Yao, Yunzhi; Ren, Dong
Abstract: A new genus and species, Reticulatitergum hui gen. et sp. nov., described from mid-Cretaceous Burmese amber, is the first record of the family Yuripopovinidae from Myanmar. The new species has unique morphological characters such as areolate body and dilated fourth antennal segment. According to the previous results of phylogenetic analysis, the taxonomic positions of the Yuripopovinidae and Dehiscensicoridae are discussed, and the latter is proposed to be synonymized with the Yuripopovinidae. The broad geographical distribution of the Yuripopovinidae in the Cretaceous suggests that they have an earlier evolutionary history which might be traced back to the Jurassic, or possibly even earlier.